Capitals, capabilities, and the conversion of commodities: the case of neurodivergent graduates’ transitions to the labour market - Tomlinson, Michael; Vincent, Jonathan (Springer Science and Business Media LLC, 2026)
The employment opportunities and outcomes of disabled graduates has gained increased international attention among researchers, policymakers and HE practitioners. This article explores the early employment transitions and experiences of neurodivergent graduates, a group who have been shown to experience significant barriers in accessing competitive employment. We offer a new framework which incorporates aspects from both capabilities and capitals perspectives to appraise the personal and socially mediating influences that shape graduates’ initial labour market opportunities and outcomes. Drawing on a qualitative dataset from 228 survey responses and interview data from 14 recent neurodivergent graduates, we analyse the experiences of graduates to understand how they convert the graduate capitals they have garnered in HE into meaningful capabilities and employment functionings. As such, this article adds empirical insight and conceptual novelty in illuminating the personal, contextual and environmental conversion factors which facilitate and/or constrain early career outcomes. Our findings raise implications for policymakers, practitioners, and employers in the UK and beyond for supporting neurodivergent graduates towards developing meaningful employment outcomes.